Corridor displays in glass cabinets - Matthews, L.D. (American Journal of Physics, 1976)
Keywords: dept.phy

Total Reflection in a Moving Medium - Porter, W.S. (American Journal of Physics, 1972)
Keywords: dept.phy

Improving the Small Hole Air Track and Table - Chonacky, N.J.; Snyder, J.W.; Matthews, L.D. (American Journal of Physics, 1971)
Keywords: dept.phy

Ultra-violet argon dayglow lines in the atmosphere of mercury - Zeelik, Michael; Dalgarno, Alexander (Planetary and Space Science, 1973)
We investigate the response of an atmosphere of argon to solar ultra-violet radiation. With the assumption that Mercury has an argon atmosphere that is optically thick to ionizing radiation the intensities of the ultra-violet dayglow lines resulting from photoelectron impact are calculated. For most of the model atmospheres, the predicted intensities are above the detection threshold of the 1973 Venus-Mercury ultra-violet spectrometer of Broadfoot, McElroy and Belton. © 1973.
Keywords: dept.phy